2014
DOI: 10.1111/ajt.12797
|View full text |Cite
|
Sign up to set email alerts
|

Immunological Status of Isolated Lymphoid Follicles After Intestinal Transplantation

Abstract: Intestinal transplantation (ITx) faces the challenge of grafting a high immunogenic organ, which is certainly one of the major obstacles for intestinal allograft acceptance. The allograft has to guarantee the proper functioning of the mucosal immune machinery under immunosuppressive conditions. Recently, it has been elucidated that isolated lymphoid follicles (ILFs) are an indispensable part of mucosal immunity to maintain IgA synthesis and consequently to control commensal microflora. No data about these foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 48 publications
1
32
0
Order By: Relevance
“…1C) and donor graft lymphocytes persisted much longer than previously reported (Fig. 1 B-C and S2)( 11, 12 ).…”
Section: Resultssupporting
confidence: 54%
See 2 more Smart Citations
“…1C) and donor graft lymphocytes persisted much longer than previously reported (Fig. 1 B-C and S2)( 11, 12 ).…”
Section: Resultssupporting
confidence: 54%
“…However, little is known about how HvG and GvH responses influence the turnover, phenotype and repertoire of tissue-resident T-cell populations following transplantation. Studies in mice( 10 ) and humans( 11 ) have indicated that recipient-derived T cells repopulate the GALT (Gut-Associated Lymphoid Tissues) of intestinal allografts early after transplantation. However, the turnover rate of mucosal T cells after intestinal transplantation has been investigated in only a few patients( 12 ) in cross-sectional studies( 11 ), without phenotype or repertoire analysis( 11, 12 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This has been done previously for investigation of chimerism in peripheral blood after transplantation by our group (28), but previous investigation of chimerism in transplanted intestinal tissue has instead relied on genetic analysis via fluorescent in situ hybridization (FISH), polymerase chain reaction (PCR), or immunohistochemistry (3, 4, 29, 30). Our method allows dynamic and in depth analysis of ILC chimerism and phenotyping.…”
Section: Discussionmentioning
confidence: 99%
“…23 Antibodies enrolled in this study are listed in Table 2. Tissue sections were deparaffinized following standard procedures as previously described.…”
Section: Immunohistochemistrymentioning
confidence: 99%